Analisa Penerapan Akuntansi Pertanggung Jawaban Dalam Menilai Kinerja Pusat Biaya (Studi Kasus Pada Penjualan Fashion Big Indoka Batik) - Purwanti Purwanti; Alfi Zahra Laila; Alika Shafa Eka Kamila; Larasati Ayundani Rahmadan; Lutfiah Oktaviani; Maryuti Azzahra Putri; Muhammad Salim; Oki Fitriani; Salwa Nabillah Bahrudin; Sindy Sartika (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
The purpose of this study was to determine the application of Indoka Batik's accountability principles as an instrument for assessing cost center performance. The research method used was a qualitative case study approach. Data collection techniques included observation, interviews, and document management to obtain valid and relevant data. The results showed that the implementation of accountability obligations at Indoka Batik was successful. This was illustrated by a clear organizational structure, a planned budget preparation process, appropriate cost classification, and a transparent cost reporting system. These four aspects are indicators that accountability is used as a basis for performance assessment and management decisions. Accountability accounting emphasizes the responsibility of each unit within the organization and manages activities and resources under control. Furthermore, this principle also provides financial performance measures as the primary instrument for assessing the effectiveness and efficiency of administrative task implementation. However, this study also revealed operational inefficiencies, as measured by a 5°C budget deviation during the 2020-2023 period. This statement has indicated the importance of assessing and improving budgeting and management processes for future cost management.